Here I am using the below code for a simplification.
DB = (Sigma)*(Sigma)*(Phi)*(Phi) BB = Sqrt(DB) // FullSimplify // PowerExpand g = 1/DB (Alpha)I = a(Phi) (Alpha) = (Alpha)I - 0.5*BB*D(BB, (Phi)) (Alpha)s = (Alpha) - ((1/2)*BB*D(BB, (Phi))) UG = 0.375 (Sigma)^2 Phi = UG - ((1/2)*(g*(Alpha)s*(Alpha)s)) // FullSimplify // PowerExpand
But I am getting a result without cancelling the common term $$phi $$
Below is what I am getting. But I need to cancel the common terms. Here $$a, sigma $$are constants. $$phi$$ is a variable
Result I got: